Ramona forever [compact disc, unabridged] - Cleary, Beverly (HarperCollins Childrens, 2010)
When Howie Kemp's mysterious Uncle Hobart comes to town, it brings some changes into Ramona Quimby's world. Howie and his sister will now only talk about their uncle. Ramona also gets the feeling that her mother and Aunt Bea are keeping some kind of secret. Through it all, Ramona makes many discoveries, including two very special ones.